2014
DOI: 10.17221/125/2013-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to rusts (Uromyces pisi and U. viciae-fabae) in pea

Abstract: Barilli E., Sillero J.C., Prats E., Rubiales D. (2014): Resistance to rusts (Uromyces pisi and U. viciae-fabae) in pea. Czech J. Genet. Plant Breed., 50: 135-143.Pea is the second most important food legume crop in the world. Rust is a pea disease widely distributed, particularly in regions with warm, humid weather. Pea rust can be incited by Uromyces viciae-fabae and by U. pisi. U. viciae-fabae prevails in tropical and subtropical regions such as India and China, while U. pisi prevails in temperate regions. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The fungal class Pucciniomycetes (formerly known as Urediniomycetes) of the Basidiomycota phyla contains most plant pathogens that cause fungal rust (Swann et al 2001). In this study, we found the presence of the wheat leaf rust fungi Puccinia recondita and faba-beans rust fungi Uromyces viciae-fabae (Barilli et al 2014) (belonging to the fungal class Pucciniomycete) in the bioaerosol samples. Hence, it was evident that the wheat eld in the study region was susceptible to brown leaf rust infection.…”
Section: Discussionmentioning
confidence: 58%
“…The fungal class Pucciniomycetes (formerly known as Urediniomycetes) of the Basidiomycota phyla contains most plant pathogens that cause fungal rust (Swann et al 2001). In this study, we found the presence of the wheat leaf rust fungi Puccinia recondita and faba-beans rust fungi Uromyces viciae-fabae (Barilli et al 2014) (belonging to the fungal class Pucciniomycete) in the bioaerosol samples. Hence, it was evident that the wheat eld in the study region was susceptible to brown leaf rust infection.…”
Section: Discussionmentioning
confidence: 58%
“…Infecting plants produce pseudo flowers, similar to true flowers in colour and shape and also leaves at the top of stem appear in rosette pattern (PFUNDER and ROY, 2000). Many authors have described rust symptoms on pea (BARILLI et al, 2009;BARILLI et al, 2014;KUSHWAHA et al, 2006;KUSHWAHA et al, 2010;CHAND et al, 2006;XUE et al, 2002). In pea plant, early rust symptoms develop on abaxial side of older leaves and form round to oval aecidia.…”
Section: Rustmentioning
confidence: 99%
“…Despite being widely used, visual DS estimations can be imprecise and biased for diseases with small and numerous lesions like rust [ 25 ]. Therefore, researchers usually also analyse IF and/or PS that are less prone to user bias to quantify more precisely partial resistance in pea [ 71 ]. Some previous studies reported the estimation of some of these disease components through RGB image analysis with variable efficiency [ 38 , 62 , 72 , 73 ].…”
Section: Processing Time Optimizationmentioning
confidence: 99%